Effects of Platelets Addition on Tension and Elasticity of the Fibrin Glue (Iraqi Journal of Medical Sciences, 2024)
Background: A biodegradable, biocompatible and natural topical tissue adhesive fibrin glue, help in starting and replicating the last phases of the coagulation cascade. The platelets contain thrombosthenin, actin and myosin filaments, which when activated produces tension and motion that is similar to that produced by skeletal muscle.Objective: To create the fibrin glue both with and without the addition of platelets, and investigate the biomechanical behavior of both formulas in terms of tension and stretching (elasticity). Methods:Creating the "ordinary fibrin glue" by using fibrinogen (from cryoprecipitate) and thrombin. In a different preparation, platelets were added to the cryoprecipitate and thrombin to create "platelets added fibrin glue". Next, the elasticity and tension of the synthetic fibrin glue were assessed—both regular and platelet-added fibrin glue—at various times using displacement and force sensors.Results: When platelets are added to fibrin glue, the elasticity outcomes at one hour and one week are significantly reduced. As well as, there were a significant higher tension results were observed at one-hour and one-week intervals when comparing regular fibrin glue with platelets added.Conclusion: The inclusion of platelets caused the glue's biological behavior to alter, showing as an increase in tension and a decrease in elasticity (stretching). When the applicator has to use this mixture to manage various body parts (such as bone regeneration, graft stabilization, regeneration of periodontal ligament and treating joints arthritis), this modification should be taken into account.Keywords: Fibrin glue, Platelets, tension, elasticityCitation: Mahmood IA, Al-Ani FS. Effects of platelets addition on tension and elasticity of the fibrin glue. Iraqi JMS. 2024; 22(1): 115-122. doi: 10.22578/IJMS.22.1.13
Keywords: Fibrin glue; Platelets; tension; elasticity